The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1055/a-1289-9059
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Training-load Quantification in Elite-level Soccer: Contextual Factors

Abstract: The aims of this study were to analyse the physical responses of professional soccer players during training considering the contextual factors of match location, season period, and quality of the opposition; and to establish prediction models of physical responses during training sessions. Training data was obtained from 30 professional soccer players from Spanish La Liga using global positioning technology (N=1365 performances). A decreased workload was showed during training weeks prior to home matches, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…11,12 Concerning to the workload developed by players in match across the season, this study showed variability between the different metrics analysed: whereas players covered a greater m-TD in the middle period compared to the other periods, the highest m-HIRD and m-SPD were found in the final period of the season. The literature shows controversy about the season period: several authors showed higher total distance and high-intensity distance covered in the final period compared to the first and middle period, 15,17 Guerrero-Calder on et al 2 found the greatest TL in the middle period, whereas other authors have found no significant TL variations over the season. 7 These discrepancies between authors may be due to the different leagues analysed; Mohr et al 17 and Rampinini et al 15 analysed the Italian First Division, J. Malone et al 7 analysed the English Premier League, Guerrero-Calder on et al 2 analysed the Spanish First Division and the present study was performed with Spanish First and Second Division teams.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…11,12 Concerning to the workload developed by players in match across the season, this study showed variability between the different metrics analysed: whereas players covered a greater m-TD in the middle period compared to the other periods, the highest m-HIRD and m-SPD were found in the final period of the season. The literature shows controversy about the season period: several authors showed higher total distance and high-intensity distance covered in the final period compared to the first and middle period, 15,17 Guerrero-Calder on et al 2 found the greatest TL in the middle period, whereas other authors have found no significant TL variations over the season. 7 These discrepancies between authors may be due to the different leagues analysed; Mohr et al 17 and Rampinini et al 15 analysed the Italian First Division, J. Malone et al 7 analysed the English Premier League, Guerrero-Calder on et al 2 analysed the Spanish First Division and the present study was performed with Spanish First and Second Division teams.…”
Section: Discussionmentioning
confidence: 97%
“…The literature shows controversy about the season period: several authors showed higher total distance and high-intensity distance covered in the final period compared to the first and middle period, 15,17 Guerrero-Calder on et al 2 found the greatest TL in the middle period, whereas other authors have found no significant TL variations over the season. 7 These discrepancies between authors may be due to the different leagues analysed; Mohr et al 17 and Rampinini et al 15 analysed the Italian First Division, J. Malone et al 7 analysed the English Premier League, Guerrero-Calder on et al 2 analysed the Spanish First Division and the present study was performed with Spanish First and Second Division teams. Nonetheless, these results also showed the lowest values in the initial period for all metrics (m-TD, m-HIRD and m-SPD).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations